The Geochemistry of Stable Chlorine and Bromine Isotopes - Eggenkamp, Hans. (Advances in Isotope Geochemistry,, 2014)
This book provides detailed information on the history, analysis and applications of chlorine and bromine isotope geochemistry. Chlorine and bromine are geochemically unique as they prefer to exist as single charged negative ions. For this reason isotope fractionation reflects mostly processes that are not related to changes in the redox state and this fractionation is generally modest. The book will describe the processes that are most easily detected using these isotopes. Also isotope variations, and processes that cause them, measured in oxidised species such as perchlorates and in organic molecules will be described in this book.